2022
DOI: 10.1107/s2056989022000111
|View full text |Cite
|
Sign up to set email alerts
|

Redetermination of the structure of 2-amino-8-thia-1,5-diazaspiro[4.5]dec-1-en-5-ium chloride monohydrate

Abstract: The reaction of β-(thiomorpholin-1-yl)propioamidoxime with tosyl chloride in CHCl3 in the presence of DIPEA when heated at 343 K for 8 h afforded the title hydrated salt, C7H14N3S+·Cl−·H2O, in 84% yield. This course of the tosylation reaction differs from the result of tosylation obtained for this substrate at room temperature, when only 2-amino-8-thia-1,5-diazaspiro[4.5]dec-1-ene-5-ammonium tosylate was isolated in 56% yield. The structure of the reaction product was established by physicochemical methods, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition, the ortho -nitrobenzenesulfochlorination of β-(thiomorpholine-1-yl)propioamidoxime ( 3 ) has the following features: at room temperature, a mixture of 2-aminospiropyrazolylammonium ortho -nitrobenzenesulfonate and chloride ( 13a and 13b ) were obtained, and carrying out the reaction at 70 °C only produces chloride 13b ( Figure 2 ). Compound 13b was previously characterized by us [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ortho -nitrobenzenesulfochlorination of β-(thiomorpholine-1-yl)propioamidoxime ( 3 ) has the following features: at room temperature, a mixture of 2-aminospiropyrazolylammonium ortho -nitrobenzenesulfonate and chloride ( 13a and 13b ) were obtained, and carrying out the reaction at 70 °C only produces chloride 13b ( Figure 2 ). Compound 13b was previously characterized by us [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…When establishing the structure of nitrobenzenesulfochlorination products, a difference was noted in the values of the mobility index R f for the products produced by the nitrobenzenesulfochlorination of amidoximes with six-membered nitrogenous heterocycles in the β-position ( 6 – 9 , 11 – 14 ) and for the para -nitrobenzenesulfoderivative of β-(benzimidazol-1-yl)propioamidoxime ( 10 ) ( R f 0.01–0.12 and 0.75). Compounds 7 and 13b were previously described in [ 7 ] and [ 26 , 27 ], respectively ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In accord with the X-ray data, in the course of the roomtemperature synthesis, solid tosylates 6-10 were obtained. From the reaction mixture heated to the boiling point of the solvent, salts 7ÁH 2 O, 8b (Kayukova et al, 2022b), 6 and 9, and compound 10 were obtained. Thus, a high synthetic temperature allows crystallization of the target salts in the form of hydrates, and the chloride-containing salt was obtained only for the thiomorpholine-containing precursor.…”
Section: Molecular Structuresmentioning
confidence: 99%
“…Recently, we found that tosylation of -(thiomorpholin-1yl)propioamidoxime at the boiling point of chloroform used as solvent afforded 2-amino-8-thia-1,5-diazaspiro[4.5]dec-1-en-5ium chloride hydrate (8b; Scheme 1) instead of tosylate 8a (Kayukova et al, 2022b). In this case, in accordance with the reaction of double substitution of ions, the tosylate anion in 2-amino-1,5-diazaspiro[4.5]dec-1-en-5-ium tosylate was exchanged for the chloride anion from diisopropylethylamine (DIPEA) hydrochloride.…”
Section: Introductionmentioning
confidence: 99%